Pendampingan Belajar Membaca Al-Qur'an Dengan Metode Ummi Pada Anak Usia 7-12 Tahun Di TPQ Darussalam, Dusun Pacar, Desa Prajegan - Friska Dwi Yulina; Sri Ana; Kunti Nadiyah Salma (Social Science Academic, 2025)
This study aims to describe the process of assisting learning to read the Qur'an with the Ummi method for children aged 7-12 years at TPQ Darussalam, Pacar Hamlet, Prajegan Village. This research uses an ABCD approach that seeks sustainable development, this method also raises potential assets with qualitative methods through observation, interviews, and documentation. One of the problems faced by TPQ Darussalam is the lack of emphasis on long-short reading and correct tajweed. This can hinder children in understanding the meaning of the Qur'an in depth. Therefore, there needs to be an effort to improve the quality of learning to read the Qur'an at TPQ Darussalam, especially in terms of coaching long-short reading. The results showed that the Ummi method is effective in helping early childhood learn to read the Qur'an. Factors that influence the success of mentoring include the patience of the mentor, the use of interesting learning media, and child motivation.